A BRIEF ANALYSIS OF THE LIFE AND CREATIVITY OF CONDUCTOR ARTURO TOSKANI - Nosirov Dilmurod Tursunovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The Great creator Arturo Toscanini was not only a great conductor, but also the owner of a strong excitable character. This article briefly discusses the path of creative life, as well as its impact on personality and creativity. The peculiarities of Arturo Toscanini's creativity are revealed, although the degree of study is partial.